Prospective Study on Several Urinary Biomarkers as Indicators of Renal Damage in Children with CAKUT - Bartoli, Fabio; Pastore, Valentina; Calè, Isabella; Aceto, Gabriella; Campanella, Vittoria; Lasalandra, Carla; Magaldi, Simona; Niglio, Francesco; Basile, Angela; Cocomazzi, Raffaella (European Journal of Pediatric Surgery, 2019)
Purpose The aim of the study was to investigate urinary levels of monocyte chemotactic protein-1 (MCP-1), epidermal growth factor (EGF), β-2-microglobulin (β2M), and FAS-ligand (FAS-L) in children with congenital anomalies of kidney and urinary tract (CAKUT) disease at risk of developing glomerular hyperfiltration syndrome. For this reason, we selected patients with multicystic kidney, renal agenesia and renal hypodysplasia, or underwent single nephrectomy.Materials and Methods This prospective, multicentric study was conducted in collaboration between the Pediatric Surgery Unit in Foggia and the Pediatric Nephrology Unit in Bari, Italy. We enrolled 80 children with CAKUT (40 hypodysplasia, 22 agenetic; 10 multicystic; 8 nephrectomy) who underwent extensive urological and nephrological workup. Exclusion criteria were recent urinary tract infections or pyelonephritis, age > 14 years, presence of systemic disease, or hypertension. A single urine sample was collected in a noninvasive way and processed for measuring by enzyme-linked immunosorbent assay urine levels of MCP-1, EGF, β2M, and FAS-L. As control, urine samples were taken from 30 healthy children.Furthermore, we evaluated the urinary ratios uEGF/uMCP-1 (indicator of regenerative vs inflammatory response) and uEGF/uβ2M (indicator of regenerative response vs. tubular damage).Results These results suggest that urinary levels of MCP-1 are overexpressed in CAKUT patients. Furthermore, our findings clearly demonstrated that both uEGF/uMCP-1 and uEGF/uβ2M ratios were significantly downregulated in all patient groups when compared with the control group.Conclusion These findings further support that CAKUT patients may, eventually, experience progressive renal damage and poor regenerative response. The increased urinary levels of MCP-1 in all groups of CAKUT patients suggested that the main factor responsible for the above effects is chronic renal inflammation mediated by local monocytes.
Keywords: CAKUT; urinary biomarkers; children; MCP-1; EGF